Evaluation of etanercept (a tumor necrosis factor alpha inhibitor) as an effective treatment for joint disease in mucopolysaccharidosis type I. A case report with whole-body magnetic resonance imaging - Buchinskaya, Natalia V.; Isupova, Eugenia A.; Vechkasova, Anastasia O.; Malekov, Damir A.; Ivanov, Dmitry O.; Kostik, Mikhail M. (Frontiers in Medicine, 2024)
Summary A 12-year-old girl with mucopolysaccharidosis (MPS) type I (Gurler-Scheie syndrome, Q70X/del C683 of the IDUA gene in the compound heterozygous state) regularly received enzyme replacement therapy (laronidase) since the preclinical stage (6 months old) due to positive family history, and started etanercept treatment due to progression of joint pain and decreasing capability to walk. The patient had a significant reduction of pain in the joints and an expansion of daily physical activity without adverse events. A decrease in bone marrow edema without foci progression compared to baseline assessment was observed in the whole-body MRI. During the treatment (baseline/6 months/12 months) the following was observed: childhood health assessment questionnaire (CHAQ) index of 1.88/2.13/1.63 points; patient’s pediatric quality of life inventory (PedsQL) of 37/30/31 points; parental PedsQL of 26/27/34 points; and patient’s pain visual-analog scale (VAS) of 75/45/40, with no VAS recorded for the mother. Juvenile arthritis functional assessment report (JAFAR) scores of 35/34/8 points were observed. A significant reduction in the taking of NSAIDs was observed. In the second half of the year, the nasal breathing became normal, and remission in chronic rhinitis and adenoiditis was achieved (no infection episodes) without otitis episodes. Conclusion Etanercept in mucopolysaccharidosis type 1 is safe and well tolerated. The reduction of joint pain and increased walking capacity were observed. A decreased number of respiratory infection episodes and nasal breathing improvement were noted during the treatment. The observation shows the role of inflammation in the different aspects of MPS. Further investigations on immune system dysregulation in patients with MPS I are needed. Additional studies on the efficacy and safety of anti-rheumatic biological drugs in patients with MPSI are required.